Combination of at-home and in-office bleaching techniques: case series - Marcela Alvarez FERRETTI; Matheus KURY; Beatriz Curvello de MENDONÇA; Marcelo GIANNINI; Vanessa CAVALLI; Vanessa CAVALLI; Flávio Henrique Baggio AGUIAR (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Tooth bleaching is one of the most conservative aesthetic techniques. At-home and in-office bleaching may be performed, as well as the combination of both techniques. As this combination may be done in different manners, distinct orders of combinations were proposed in this report. A 24 years-old man, whose upper central incisor and canine shades were A2 and A3 respectively, was initially treated by chair-side with 40-min application of 40% hydrogen peroxide (HP) for two sessions. Afterwards, an two-week overnight at-home bleaching was performed with 10% carbamide peroxide (CP). The shade of upper central incisors changed to 1M1 and canine was B1. Conversely, a 30 years-old woman was firstly conducted with at-home bleaching (overnight 4-weeks 10% CP) and, subsequently, with a single appointment of in-office bleaching for 45 minutes (35% HP). The shade of her upper central incisor changed from A1 to 0.5M1 and the upper canine from A3 to B1. The VITA classical (A1-D4) shade guide and VITA Bleached guide 3D-MASTER were used to determine the tooth color during the treatments. In both bleaching treatments, patients reported no significant tooth sensitivity and the final outcomes met their expectation.